Adonis sp., Convallaria sp., Strophanthus sp., Thevetia sp., and Leonurus sp. - Cardiotonic Plants with Known Traditional Use and a Few Preclinical and Clinical Studies - Erdogan Orhan, Ilkay; Gokbulut, Alper; Sezer enol, Fatma (Current Pharmaceutical Design, 2017)
Plants have been always a fruitful source of active metabolites against many human disorders, where cardiovascular (CV) diseases have been one of the major health problems all over the world. There are some clinically proved medicinal plants with cardioprotective effects such as Crataegus monogyna and C. oxyacantha (hawthorn) from Rosaceae. On the other hand, cardiac glycosides, present in a number of plant species, are wellknown for their cardiotonic activity. However, we encountered such a fact that very less number of studies are available on the source plants; e.g. Adonis vernalis, Convallaria majalis, Strophanthus kombe, Thevetia peruviana, Leonurus cardiaca, etc. Consequently, we herein aimed to cover all available data consisting of in vitro, in vivo, and human studies (if any) on cardiotonic effects of the aforementioned species through a wide literature search using Scopus, Web of Science as well as Pubmed.
Keywords: Convallaria majalis